Everyday time travel: Temporal mobility and multitemporality with smartphones - Firth, Roxana Morosanu; Rintel, Sean; Sellen, Abigail (Making Time for Digital Lives: Beyond Chronotopia, 2020)
How have you last checked the time? Chances are that you did not need a specialized technology, such as a watch or a clock, because the device you are using to read this text on might display the time on one corner of the screen or another. These days it is almost impossible to not know the time. Most, if not all, digital technologies, from fitness trackers to smart TVs, have an incorporated time feature that shows the satellite-determined exact time. This chapter argues that while situating everyday life in relation to a globally precise time, digital technologies can also be creatively employed to unsettle time—to jump from present to past and future, or to juxtapose moments to create unique temporal experiences. The accounts discussed here focus on the temporal experiences of people in full-time employment working in the fast-paced sector of technology. In these contexts, the tool that is specifically employed to navigate and manipulate time is the smartphone. Cite as: Roxana Morosanu Firth, Sean Rintel, and Abigail Sellen. 2020. Everyday time travel: Temporal mobility and multitemporality with smartphones. In Making time for digital lives : Beyond Chronotopia, Anne Kaun, Christian Pentzold, and Christine Lohmeier (eds.). Rowman & Littlefield, 103–116.